2016
DOI: 10.11646/zootaxa.4173.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The first riparian skink (Genus: Sphenomorphus Strauch, 1887) from Peninsular Malaysia and its relationship to other Indochinese and Sundaic species

Abstract: Recently discovered populations of skinks of the genus Sphenomorphus from central Peninsular Malaysia represent a new species, S. sungaicolus sp. nov., and the first riparian skink known from Peninsular Malaysia. Morphological analyses of an earlier specimen reported as S. tersus from the Forest Research Institute of Malaysia (FRIM), Selangor indicate that it too is the new riparian species S. sungaicolus sp. nov. Additionally, two specimens from the Tembat Forest Reserve, Hulu Terengganu, Kelantan and another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…The species Isopachys clustered into a clade with the Tropidophorus genus and not with the Sphenomorphus genus, a result that is different from some previous conclusions [ 12 , 44 , 69 , 73 ]. Using 12S and 16S RNAs, the clades (( Isopachys + ( Sphenomorphus + ( Lipinia + Scincella ))) + Tropidophorus ) were supported in BI, ML, and maximum parsimony (MP) trees constructed by Honda et al [ 73 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The species Isopachys clustered into a clade with the Tropidophorus genus and not with the Sphenomorphus genus, a result that is different from some previous conclusions [ 12 , 44 , 69 , 73 ]. Using 12S and 16S RNAs, the clades (( Isopachys + ( Sphenomorphus + ( Lipinia + Scincella ))) + Tropidophorus ) were supported in BI, ML, and maximum parsimony (MP) trees constructed by Honda et al [ 73 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Using 12S and 16S RNAs, the clades (( Isopachys + ( Sphenomorphus + ( Lipinia + Scincella ))) + Tropidophorus ) were supported in BI, ML, and maximum parsimony (MP) trees constructed by Honda et al [ 73 ]. Although the same genes were used (12S and 16S RNA) in the phylogenetic analysis of Peninsular Malaysia skinks, Rizal et al found that the clade of ((( Tropidophorus + Sphenomorphus ) + Lipinia ) + Isopachys ) was supported in both ML and BI trees [ 12 ]. These differences in topological structures may be related to the amount of data used to construct the phylogenetic tree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grismer et al 2017a) of Tytthoscincus from Peninsular Malaysia and not members of the lowland swamp clade (sec. Grismer et al 2016Grismer et al , 2017b nor are they each other's closest relatives despite their occurrence in the same area (Fig. 4).…”
Section: Resultsmentioning
confidence: 84%
“…In contrast, a few new discoveries on various faunal groups were made here. Several new species of crabs (Ng and Ahmad 2016;Ng 2020) and skinks species (Grismer et al 2014(Grismer et al , 2018Sumarli et al 2016) had been made from SLF, implying that the diversity of fauna and more specifically reptiles, is high in this underexplored forest.…”
Section: Introductionmentioning
confidence: 99%